1999
DOI: 10.1063/1.370209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thin V insertion layer into Ta film on the performance of Ta diffusion barrier in Cu metallization

Abstract: In order to increase the failure temperature of Ta diffusion barrier for Cu, we investigated the effect of a thin V insertion layer ͑100 Å͒ into Ta film with/without ion bombardment on Ta diffusion barrier performance in Cu metallization. When the Ta/V/Ta diffusion barrier was deposited without concurrent ion bombardment, the insertion of the thin V layer into Ta film was not effective to improve the barrier performance of Ta film, because of the thermal instability of the Ta/V/Ta multilayer caused by the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Thus, it is concluded that Cu diffusion into silicon promotes TaSi 2 grain growth [81]. Further possibilities include the incorporation of CeO 2 into Ta grain boundaries [87] as well as the insertion of an additional Zr [88] or V film [89] into the Ta barrier. Yin et al [83] demonstrated that heat treatment in vacuum at pressure p 0 ≈ 1 Pa leads to O diffusion along Cu grain boundaries into the Cu/Ta interface and, consequently, to the formation of a thin amorphous Ta oxide layer.…”
Section: Pure Ta Diffusion Barriersmentioning
confidence: 99%
“…Thus, it is concluded that Cu diffusion into silicon promotes TaSi 2 grain growth [81]. Further possibilities include the incorporation of CeO 2 into Ta grain boundaries [87] as well as the insertion of an additional Zr [88] or V film [89] into the Ta barrier. Yin et al [83] demonstrated that heat treatment in vacuum at pressure p 0 ≈ 1 Pa leads to O diffusion along Cu grain boundaries into the Cu/Ta interface and, consequently, to the formation of a thin amorphous Ta oxide layer.…”
Section: Pure Ta Diffusion Barriersmentioning
confidence: 99%